2022
DOI: 10.1161/jaha.122.027373
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of BAG3: A Paradigm for Developing Precision Therapies for Dilated Cardiomyopathies

Abstract: Nonischemic dilated cardiomyopathy is a common form of heart muscle disease in which genetic factors play a critical etiological role. In this regard, both rare disease‐causing mutations and common disease‐susceptible variants, in the Bcl‐2–associated athanogene 3 ( BAG3 ) gene have been reported, highlighting the critical role of BAG3 in cardiomyocytes and in the development of dilated cardiomyopathy. The phenotypic effects of the BAG3 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 101 publications
0
12
0
Order By: Relevance
“…Similar gene-specific or targeted molecular treatments are expected to be developed for other genetic causes of cardiomyopathy too with the expectations of achieving disease cure or complete reversal. 77 Precision medicine depends on precision diagnostics and next to genotyping, imaging is equally important for patient selection and in assessing the efficacy of existing or novel treatments. Given its high reproducibility for volumetric measurements, CMR has a primary role in assessing the efficacy of treatment interventions and is used by clinical trials to assess soft clinical end points.…”
Section: Imaging and Genetics For Patient Selection And The Deploymen...mentioning
confidence: 99%
“…Similar gene-specific or targeted molecular treatments are expected to be developed for other genetic causes of cardiomyopathy too with the expectations of achieving disease cure or complete reversal. 77 Precision medicine depends on precision diagnostics and next to genotyping, imaging is equally important for patient selection and in assessing the efficacy of existing or novel treatments. Given its high reproducibility for volumetric measurements, CMR has a primary role in assessing the efficacy of treatment interventions and is used by clinical trials to assess soft clinical end points.…”
Section: Imaging and Genetics For Patient Selection And The Deploymen...mentioning
confidence: 99%
“…In a group of similarly large GWAS studies, the BAG3 locus was associated with dilated cardiomyopathy [ 93 ]. Most recently, we reported that all of the known pathogenic/likely pathogenic variants affect at least one of three protein functional domains: the WW domain, the second IPV (Il-Pro-Val) domain, or the BAG domain; whereas none of the missense pathogenic/likely pathogenic variants affect the proline-rich repeat (PXXP) domain [ 7 ]. A common variant, p.Cys151Arg, associated with reduced susceptibility to dilated cardiomyopathy, demonstrated a significant difference in allele frequencies among diverse human populations, suggesting evolutionary selective pressure.…”
Section: Bag3 In Heart and Skeletal Musclementioning
confidence: 99%
“…BAG3 is one of six proteins in the BAG family. All of these proteins share a BAG domain that binds to the ATPase binding site on heat shock protein 70 (Hsp/Hsc 70), yet each appears to play a unique role in the cell [ 7 ] ( Figure 1 ). All of the BAG family of proteins are constitutively expressed but are regulated independently.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes there may be an overlap with other types of cardiomyopathies, which share a profound propensity for arrhythmic events. 20 The best studied gene variants and their association with the clinical phenotype and the risk of SCD are presented in Table 1, [21][22][23][24][25][26] whilst an overlapping genetic background of different types of cardiomyopathies is presented in Figure 1. Genetic testing and counselling should be offered to all patients with DCM (and other cardiomyopathies) as it can aid in diagnosis, risk assessment, prognostication and reproductive decisions, and serve to initiate cascade genetic screening of the relatives.…”
Section: Genetic Backgroundmentioning
confidence: 99%